Human Bocavirus in Korean Children with Gastroenteritis and Respiratory Tract Infections - Lee, Eun Jin (Biomed Res Int, 2016)
Human bocaviruses (HBoVs) are suggested to be etiologic agents of childhood respiratory and gastrointestinal infections. There are four main recognized genotypes of HBoVs (HBoV1–4); the HBoV-1 genotype is considered to be the primary etiologic agent in respiratory infections, whereas the HBoV2–4 genotypes have been mainly associated with gastrointestinal infections. The aim of the present study was to determine the distribution of HBoV genotypes in children with respiratory or gastrointestinal infections in a hospital in Korea. A total of 662 nasopharyngeal swabs (NPSs) and 155 fecal specimens were collected from children aged 5 years or less. Polymerase chain reaction (PCR) was conducted to detect the NS1 HBoV gene. The VP1 gene of HBoV was further amplified in samples that were positive for the NS1 gene. The PCR products of VP1 gene amplification were genotyped by sequence analysis. HBoV was detected in 69 (14.5%) of 662 NPSs and in 10 (6.5%) of 155 fecal specimens. Thirty-three isolates from NPSs and five isolates from fecal specimens were genotyped, and all 38 sequenced isolates were identified as the HBoV-1 genotype. HBoV-1 is the most prevalent genotype in children with respiratory or gastrointestinal HBoV infections in a hospital in Korea.